Selection of bacteria inducing calcium carbonate precipitation for self-healing concrete application - Ridwan Syarif; Ridho Kresna Wattimena; Intan Nurul Rizki; Siti Khodijah Chaerun (Institut Teknologi Bandung, 2019)
A modification of bacterial medium using calcium lactate pentahydrate was developed for calcium carbonate precipitation. A total of five strains of bacteria were cultivated on the solution medium containing nutrient broth and calcium lactate pentahydrate. In this study, the variation of 3.2 mM and 16.2 mM of calcium lactate pentahydrate was used to obtain the optimum condition for bacterial growth. The results showed that isolated strains CPB 1, CPB 3, and CPB 5 with medium containing nutrient broth and 3.2 mM calcium lactate pentahydrate gave the optimum growth, pH and Eh, thus being favourable for the process of calcium carbonate precipitation. Hence, this will be useful for self-healing concrete.